The social issue and military regimes. Argentina and Chile during the seventies (Quinto Sol, 2015)
This article analyzes social policies implemented by Secretary of Community Promotion and Assistance of Social Welfare Ministry during “Argentine Revolution” and the Direction of Civil Organizations and the Ministry of the Interior during the Chilean dictatorship (1973-1988) aimed to obtain social consensus. This work expects to make a complex analysis on the concept of “Authoritarian-bureaucratic State”, applied to the study of Southern Cone dictatorships. The hypothesis to be tested is that Ongania and Pinochet’s regimes sought to organize popular sectors under new social frames and not just to repress them.
Keywords: social policy; dictatorships; consensus; Onganía; Pinochet